Plan de negocios para la implementación de una microempresa productora de gritz y harina de maíz (zea mays), Los Amarillos-Tosagua - Alcívar Rodríguez, Darwin Manuel (2013)
The main objective of this study was to conduct a business plan for the implementation of a microenterprise producer of Gritz and cornmeal (Zea Mays), on the site Los Amarillos in Tosagua canton. The market research was applied to cereal producer companies located in Quito and cornmeal producer in Chone. Market research showed an acceptance of 87% with a total demand of 10832.5 tons/month, corn as raw material for Gritz is 60%, 40% flour, for the design of machinery INMEGAR workshops were visited, and contacts China now for the construction of the plant was considered 150 m2 the amount of production was determined that the plant will have 3 operators, a secretary, a chief of production and a manager. The Leopold matrix show 23 positive environmental impacts and 12 negative impacts. The investment for the project is $ 69,886.88, the balance point is 57 qq which 34 are of Gritz and 23 of cornmeal, selling all production profits the first year will be $ 25,292.48 and the flow for the first year will be $ 31,998.49. The VNA was $ 303,982.89 and TIR 71%, the PRI was 1.89 years. According to studies it was determined that the project is viable because the VNA is greater than zero.